2017
DOI: 10.2527/jas.2017.1530
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Communication: Ranking dairy cows for methane emissions measured using respiration chamber or GreenFeed techniques during early, peak, and late lactation1

Abstract: Our objective was to compare the ranking of dairy cows according to their methane (CH) emissions as measured by a respiration chamber (RC) technique and the GreenFeed (GF) technique during 3 periods in second lactation. Two-day CH measurements in a RC performed in wk 3, 14, and 42 of lactation were flanked by GF measurements for 20 (period 1 [P1]), 35 (period 2 [P2]), and 35 (period 3 [P3]) days, respectively, before and after RC measurement. This gave the total duration of CH measurements using the GF system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The between-cow variability enabled the cattle to be individually ranked creating 5 groups that differed significantly in MY. Others have ranked dairy cows according to MY using the GF system (Rischewski et al, 2017;Coppa et al, 2021), but we are unaware of other published studies that report MY rankings of beef cattle. The 36.6% difference in MY between the top and bottom groups substantiates the variation reported by Difford et al (2018) for 750 lactating Holstein dairy cows from commercial herds using infrared gas analyzers installed on automatic milking machines.…”
Section: Figurementioning
confidence: 94%
See 2 more Smart Citations
“…The between-cow variability enabled the cattle to be individually ranked creating 5 groups that differed significantly in MY. Others have ranked dairy cows according to MY using the GF system (Rischewski et al, 2017;Coppa et al, 2021), but we are unaware of other published studies that report MY rankings of beef cattle. The 36.6% difference in MY between the top and bottom groups substantiates the variation reported by Difford et al (2018) for 750 lactating Holstein dairy cows from commercial herds using infrared gas analyzers installed on automatic milking machines.…”
Section: Figurementioning
confidence: 94%
“…Methane production (MP; g/d) is a function of dry matter (DM) intake (DMI), diet composition, rumen fermentability and the animal's genetics, physiology and microbiome (Beauchemin et al, 2020). Consequently, it varies during the production cycle of the animal (Rischewski et al, 2017;Coppa et al, 2021). Numerous thorough reviews have discussed possible enteric CH 4 mitigation strategies (e.g., Hristov et al, 2013;Beauchemin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feed intake depression during the RC period was expected to occur despite the adaptation, due to the nature of cows being housed in individual RC (e.g., social eating, movement in freestalls, ambient temperature). In previous studies involving RC, the typical drop in feed intake is approximately 1 to 2 kg DMI (Alemu et al, 2017;Rischewski et al, 2017). To estimate the drop in intake during the RC period, the expected DMI if cows were in freestalls was estimated by averaging DMI values ±1 wk relative to the RC period for each cow and multiplying this value by 23 h/24 h (estimated DMI/23 h).…”
Section: Experimental Design and Animal Managementmentioning
confidence: 99%
“…Reliable results can be obtained if the timing and times of each animal measurement are well controlled, which is easily achievable by the operation of an investigator in a tie stall barn [ 65 ]. GreenFeed is capable of differentiating the higher emitters from the lower ones in dairy cows and beef heifers as RC [ 39 , 66 ]. Huhtanen et al [ 67 ] reported that CH 4 production measured by GF was significantly correlated with that by RC (R 2 = 0.92) in direct comparisons and also in line with CH 4 emissions calculated by prediction equations developed by RC data.…”
Section: Measurement Techniquesmentioning
confidence: 99%